'The unmasking of modern science' – the sequel (II) - Walt, J. L. van der (Koers, 2006)
In 1982, T.M. Moore claimed that positivism was in the process of being “unmasked”. Its shortcomings were being unmasked by its enemies as well as by its adherents. In describing the process of unmasking, Moore resorted to T.S. Kuhn’s sociological theory of normal science, paradigms, crises and revolutions. Moore then went on to challenge the Christian scholarly community to (inter alia) develop a new paradigm for science. Now, after just more than two decades have elapsed since this exhortation by Moore, a survey had to be done to see to what extent the secular as well as the Christian community has taken up the challenge and how both of them have progressed in the directions that Moore had predicted. It has also become time for the Christian community to assess its own progress towards developing a “new” scientific paradigm. In this, the second part of a two-part article on this subject, the author attends not only to how the Christian community took up Moore’s challenges, but also to how Christian scholars tried to avoid the pitfalls of secularism, postmodern fragmentation and a preference for contingent foundations, which have become the characteristic features of modern science, as outlined in part I of this article.